Phytocomponents, safety, antioxidant, anti-inflammatory, hypocholesterolemic and anti-atherosclerotic properties of Basella alba L. leaf extract - Gunasekaran, Baskaran (2015)
Hypercholesterolemia is the major risk factor that leads to atherosclerosis, which is the primary cause of death in world population. Nowadays, alternative treatment using medicinal plants gained much attention since the treatment using synthetic drug, statins, lead to adverse health effects, especially liver and muscle toxicity. Thus, the focus of this study was on Basella alba leaf extract; its phytocomponents, toxicity, antioxidant, anti-inflammatory, hypocholesterolemic and anti-atherosclerotic properties. In this study, 25 medicinal plants extracts were screened for anti HMG-CoA reductase activity. B. alba leaf extract showed the highest inhibitory effect, about 74%. Therefore, B. alba was examined in order to investigate its phytochemical components. GC-MS/MS analysis detected 25 compounds while RP-HPLC revealed the presence of naringin, apigenin, luteolin, ascorbic acid and α-tocopherol. The toxicity evaluation of B. alba leaf extract using cytoxicity test against Vero and WRL-68 cell lines, acute and subchronic toxicity test in rats confirmed that B. alba extract is non toxic and can be utilized as alternative therapeutic agent. B. alba extract exhibits high antioxidant activity in inhibiting radicals like DPPH, nitric oxide and ferric ions. Anti-inhibitory activity of B. alba extract on hyaluronidase, xanthine oxidase and lipoxygenase enyzmes demonstrated a desirable anti-inflammatory activities.Twenty New Zealand white rabbits were divided into 5 groups and fed with normal diet, 2% high cholesterol diet (HCD), 2% HCD + 10 mg/kg simvastatin, 2% HCD + 100 mg/kg B. alba extract and 2% HCD + 200 mg/kg B. alba extract, respectively. The treatment with B. alba extract significantly lowered the elevated levels of TC, TG, LDL, livers enzymes (ALT and AST) and muscle enzyme (CK), and increased the level of HDL and antioxidant enzymes (SOD and GPx). B. alba extract significantly suppressed the aortic plaque formation. This is the first in vivo study on B. alba that suggests its potential as an alternative therapeutic agent for hypercholesterolemia and atherosclerosis.